Direct replacement of antibodies with molecularly imprinted polymer (MIP) nanoparticles in ELISA - development of a novel assay for vancomycin - Chianella, Iva; Guerreiro, Antonio R.; Moczko, Ewa; Caygill, J. S.; Piletska, Elena V.; Perez De Vargas Sansalvador, Isabel M.; Whitcombe, Michael J.; Piletsky, Sergey A. (American Chemical Society, 2013)
A simple and straightforward technique for coating microplate wells with molecularly imprinted polymer nanoparticles (nanoMIPs) to develop ELISA type assays is presented here for the first time. NanoMIPs were synthesized by a solid phase approach with immobilized vancomycin (template) and characterized using Biacore 3000, dynamic light scattering and electron microscopy. Immobilization, blocking and washing conditions were optimized in microplate format. The detection of vancomycin was achieved in competitive binding experiments with a HRP-vancomycin conjugate. The assay was capable of measuring vancomycin in buffer and in blood plasma within the range 0.001-70 nM with a detection limit of 0.0025 nM (2.5 pM). The sensitivity of the assay was three orders of magnitude better than a previously described ELISA based on antibodies. In these experiments nanoMIPs have shown high affinity and minimal interference from blood plasma components. Immobilized nanoMIPs were stored for 1 month at room temperature without any detrimental effects to their binding properties. The high affinity of nanoMIPs and the lack of a requirement for cold chain logistics make them an attractive alternative to traditional antibodies used in ELISA